Relevant mechanisms of MAIT cells involved in the pathogenesis of periodontitis - Jiang, Xinrong; Zhao, Qingtong; Huang, Zhanyu; Ma, Fengyu; Chen, Kexiao; Li, Zejian (Frontiers in Cellular and Infection Microbiology, 2023)
Mucosal-associated invariant T cells (MAIT cells) are a class of unconventional T cells that are abundant in the human body and recognize microbial-derived Vitamin B metabolites and rapidly produce a large number of pro-inflammatory cytokines, which are widely involved in immune responses to various infectious diseases. In the oral mucosa, MAIT cells tend to accumulate near the mucosal basal lamina and are more inclined to secrete IL-17 in an activated state. Periodontitis is a group of diseases that manifest mainly as an inflammation of the gums and resorption of the alveolar bone due to the invasion of the periodontal tissue by bacteria of plaque on the dental surface. The course of periodontitis is often accompanied by a T-cell-mediated immune response. This paper will address the nature of MAIT cells and their study in infectious diseases about periodontitis.